Growth of Ultrathin Well-Defined and Crystalline Films of Co3O4 and CoOOH by Electrodeposition. Issue 1 (1st January 2023) - Pacheco, I.; Bouvier, M.; Magnussen, O. M.; Allongue, P.; Maroun, F.
Abstract : Cobalt oxides are among the best noble metal free catalysts for the oxygen evolution reaction in alkaline electrolyte. To elucidate the origin of their catalytic properties, crystalline films with well-defined orientation and surface quality are needed. In this work, we study the growth of ultrathin crystalline films of cobalt oxides layers on Au(111). The films are grown by electrodeposition at reflux temperature in cobalt nitrate alkaline solutions in the presence of tartrate. The film structure and morphology is studied by X-ray diffraction, atomic force microscopy and scanning electron microscopy, as a function of the deposition parameters (solution composition, potential). Single phase Co3 O4 (111) and CoOOH(001) films in epitaxy with the Au(111) substrate could be obtained by choosing the conditions of deposition. The CoOOH films present a smooth morphology with several 100 nm wide pyramidal islands with stepped facets. The morphology of Co3 O4 films consists of three-dimensional densely packed triangular islands with flat tops. Finally, we investigate the influence of the substrate on the morphology of Co3 O4 films by depositing them on Au(100) and a CoOOH buffer layer. The nucleation and growth modes as well as the reaction mechanisms are discussed.